Labour Market Reallocation Effects of COVID-19 Policies in Spain: A Tale of Two Recessions - Antonia Diaz; Juan J. Dolado; Álvaro Já\~nez; Felix Wellschmied (Institute of Labor Economics (IZA), 2023)
This paper studies short-time work arrangements (ERTEs) when aggregate risk is partially sector-specific. In Spain, the Great Recession and the pandemic recession (aka the Great Contagion) can both be understood as being driven partially by large sector-specific shocks. However, the latter shows much less labor reallocation because ERTEs were available to firms. We show that ERTEs stabilize unemployment rates by allowing workers to remain with their employers in highly affected sectors. However, they crowd-out labor hoarding of employers, increase the volatility of the rate of people working and, consequently, of output, and slow-down worker reallocation away from the sectors badly hit by the recession.
Keywords: J11; J18; J21; J64; 330; worker turnover; sector diversification; short-time work; Great Recession; COVID-19